USULAN PENGALIHAN JALUR KENDARAAN GUNA MEMINIMASI ANTRIAN PADA SAAT JAM SIBUK DI SPBU PURWAKARTA - Edi Susanto; Desi Tri Sugiharti (Universitas Boyolali, 2024)
The increasing public need for fuel oil (BBM) creates quite long queues at every public fuel oil filling station (SPBU), as is the case at the SPBU-Simpang Veteran Purwakarta. Long queues occur on motorbike routes at certain times. It is suspected that the current queue is due to peak hours due to the ineffectiveness of the Regent's previous regulations regarding school entry rules which were supposed to start at 6 am and leave at 14.00 pm, which were not implemented continuously. It is possible that during peak hours motor vehicle customers who fill up their vehicles with fuel will experience quite a high increase, resulting in excessively long queues on motorbike lanes. The length of the queue makes some consumers reluctant to wait and decide to leave and leave the queue. At the same time, charging lanes for car drivers are relatively empty because the increase in car driving customers is not that high. This proposal is a solution to problems that occur during rush hours in the morning and afternoon, namely diverting 1 car lane into a lane for motor vehicles is a strategy that can reduce the problem of long queues that occur on motorbike lanes.